The Potential of HLA-G-Bearing Extracellular Vesicles as a Future Element in HLA-G Immune Biology - Rebmann, Vera; König, Lisa; Nardi, Fabiola da Silva; Wagner, Bettina; Manvailer, Luis Felipe Santos; Horn, Peter A. (Frontiers in Immunology, 2016)
The HLA-G molecule is a member of the non-classical HLA class I family. Its surface expression is physiologically restricted to the maternal-fetal interface and to immune privileged adult tissues. Despite the restricted tissue expression, HLA-G is detectable in body fluids as secreted soluble molecules. A unique feature of HLA-G is the structural diversity as surface-expressed and as secreted molecules. Secreted HLA-G can be found in various body fluids either as free soluble HLA-G or as part of extracellular vesicles (EVs), which are composed of various antigens/ligands/receptors, bioactive lipids, cytokines, growth factors and genetic information such as mRNA and microRNA. Functionally, HLA-G and its secreted forms are considered to play a crucial role in the network of immune-regulatory tolerance mechanisms, preferentially interacting with the cognate inhibitory receptors LILRB1 and LILRB2. The HLA-G mediated tolerance is described in processes of pregnancy, inflammation, and cancer. However, almost all functional and clinical implications of HLA-G in vivo and in vitro have been established based on simple single ligand/receptor interactions at the cell surface, whereas HLA-G-bearing EVs were in minor research focus. Indeed, cytotrophoblast cells, mesenchymal stem cells and cancer cells were recently described to secrete HLA-G-bearing EVs, displaying immunosuppressive effects and modulating the tumor microenvironment. However, numerous functional and clinical open questions persist. Here, we (i) introduce basic aspects of EVs biology, (ii) summarize the functional knowledge, clinical implications and open questions of HLA-G-bearing EVs and (iii) discuss HLA-G-bearing EVs as a future element in HLA-G biology.